2023
DOI: 10.3389/fenvs.2023.1154052
|View full text |Cite
|
Sign up to set email alerts
|

Literacy rate impact on innovations and environmental pollution in China

Abstract: This study examines the impact of literacy rate and innovations on environmental pollution in China from 1990 to 2021. We applied the Quantile Autoregressive Distributed Lag method for the analysis, and our findings suggest that an increase in literacy rate leads to short- and long-term innovations. At the same time, literacy has a positive effect in 1st to 4th quantile in the long run. Furthermore, innovation has a positive effect on environmental pollution. However, in the short run, the literacy rate has ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The percentage of responding interviewees/surveyees in Guangzhou was higher than that in Karachi, showing a higher public awareness level toward individual responsibilities in society among the residents of Guangzhou. The higher public awareness level can be attributed to the relatively higher educational levels (mostly university graduates) of surveyees/interviewees in Guangzhou compared with Karachi because an increased literacy rate will result in increased innovation and awareness among people [42]. The results are also in line with the findings of [43], who observed that environmental awareness among fifth-year university students was higher than that among first-year students.…”
Section: The Sociodemographic Characteristics Of Respondents In Guang...supporting
confidence: 78%
“…The percentage of responding interviewees/surveyees in Guangzhou was higher than that in Karachi, showing a higher public awareness level toward individual responsibilities in society among the residents of Guangzhou. The higher public awareness level can be attributed to the relatively higher educational levels (mostly university graduates) of surveyees/interviewees in Guangzhou compared with Karachi because an increased literacy rate will result in increased innovation and awareness among people [42]. The results are also in line with the findings of [43], who observed that environmental awareness among fifth-year university students was higher than that among first-year students.…”
Section: The Sociodemographic Characteristics Of Respondents In Guang...supporting
confidence: 78%
“…Our study thus revealed about the gender equity in activism in one hand and opined great concern about the less participation of females due to mere entertainment addiction. Literacy is an important factor for environmental awareness (Jiang et. al., 2023;Agfar et.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this it is very important for students to study and understand the factors and impacts of environmental pollution that occur around them (Jiang et al, 2023). However, the way to understand to students about the causes, impacts, and prevention of environmental pollution is certainly not so easy.…”
Section: Introductionmentioning
confidence: 99%